Measurement of digital scope using visual basic / Khaled Benjamin Baharom - Baharom, Khaled Benjamin (2009)
This paper suggests a measurement through a software programming in order to enhance the application of laboratory display equipment like oscilloscope. Laptop or PC which apply with this system could act as an output where it has a capability to display a signal produce by function generator in form of sine wave, square wave and triangle wave. There have a serial communication occurs between the laptop and input device which is oscilloscope and function generator. Graphical user interface was created to ease the user to achieve high perform provided by the system. Beside user-friendly concept were necessary and a priority between user and device. Controlling, coordinating and acquiring data from device is a common laboratory task. Processing measurements and graphically displaying results are also well within the reach the Visual Basic. Every single item provided in this system more or less enhance the quality of data measurement, continue with produce better output result and be able to come out with good yields of data management